2020
DOI: 10.1021/acsmaterialslett.0c00302
|View full text |Cite
|
Sign up to set email alerts
|

Embedding PbS Quantum Dots (QDs) in Pb-Halide Perovskite Matrices: QD Surface Chemistry and Antisolvent Effects on QD Dispersion and Confinement Properties

Abstract: Hybrid materials of metal chalcogenide colloidal quantum dots (QDs) embedded in metal halide perovskites (MHPs) have led to composites with synergistic properties. Here, we investigate how QD size, surface chemistry, and MHP film formation methods affect the resulting optoelectronic properties of QD/MHP "dot-in-matrix" systems. We monitor the QD absorption and photoluminescence throughout synthesis, ligand exchange and transfer into the MHP ink, and characterize the final QD/MHP films via electron microscopy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 60 publications
4
23
0
Order By: Relevance
“…Another additive with several advantages is embedded PbS quantum dots (QDs) into the perovskite thin films. 46 49 The chemi-structural match of PbS QDs 28 or nanoplatelets (NPLs) 50 with perovskite (MAPI or FAPI) crystal phase results in the generation of seed-like nucleation regions for the bulky-epitaxial growth of high-quality perovskite absorber with enhanced optoelectronic properties and improved long-term stability. 28 , 50 53 Although the huge interest of FAPI PSCs advancement in the stabilization of the FAPI solar cells, and the pieces of evidence that NMP improves its stability, the foundation of the improvement of the formamidinium stabilization was not yet analyzed, 23 , 26 especially beyond low RH in real ambient conditions including medium-high RH fabrication conditions and how these conditions could affect the final device stability.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another additive with several advantages is embedded PbS quantum dots (QDs) into the perovskite thin films. 46 49 The chemi-structural match of PbS QDs 28 or nanoplatelets (NPLs) 50 with perovskite (MAPI or FAPI) crystal phase results in the generation of seed-like nucleation regions for the bulky-epitaxial growth of high-quality perovskite absorber with enhanced optoelectronic properties and improved long-term stability. 28 , 50 53 Although the huge interest of FAPI PSCs advancement in the stabilization of the FAPI solar cells, and the pieces of evidence that NMP improves its stability, the foundation of the improvement of the formamidinium stabilization was not yet analyzed, 23 , 26 especially beyond low RH in real ambient conditions including medium-high RH fabrication conditions and how these conditions could affect the final device stability.…”
mentioning
confidence: 99%
“…The intermediate FAI·PbI 2 ·NMP adduct , assists the formation of smooth and pinhole-free perovskite thin films at ambient atmosphere, and the pure FAPI reaches a stabilized PCE of 16.69% stable for about 1 month at low RH < 20%. Another additive with several advantages is embedded PbS quantum dots (QDs) into the perovskite thin films. The chemi-structural match of PbS QDs or nanoplatelets (NPLs) with perovskite (MAPI or FAPI) crystal phase results in the generation of seed-like nucleation regions for the bulky-epitaxial growth of high-quality perovskite absorber with enhanced optoelectronic properties and improved long-term stability. , Although the huge interest of FAPI PSCs advancement in the stabilization of the FAPI solar cells, and the pieces of evidence that NMP improves its stability, the foundation of the improvement of the formamidinium stabilization was not yet analyzed, , especially beyond low RH in real ambient conditions including medium-high RH fabrication conditions and how these conditions could affect the final device stability. Second, the perovskite-based devices fabricated in air are not always compared with the one fabricated under nitrogen, and the stability tests were still carried out with storage under nitrogen or RH < 20%, , so the investigation of the stability of devices fabricated in both conditions is highly demanding, to shine a light on the origin of the enhanced stabilization under ambient conditions of materials normally affected by humid conditions, , in order to develop industrially friendly fabrication processes.…”
mentioning
confidence: 99%
“…A recent study demonstrated the introduction of PbS into the perovskite can be possible due to similar lattice constant and related crystal structures. For instance, the crystal structures of MAPbI 3 and PbS are tetragonal and rock-salt, respectively, with Pb being hexacoordinated in each crystal. , Moreover, a shell of PbS onto the perovskite improves black phase stability of iodide-based perovskite and reduces ionic migration in the mixed perovskite system. , These particles show extended optical response and modulation of the electronic properties from n-type to ambipolar transport, with implications for photodetector, photovoltaic, and NIR LED applications. Sargent et al and other researchers reported another study by embedding the PbS NCs into the bulk matrix of perovskite (hybrid and all-inorganic) for improved optoelectronic properties and the phase stability of iodide based perovskite. , The size and composition of the CsPbX 3 NCs and its relative alignment to the band structure of PbS could form two types of energy band alignment, named type I and type II. Type I promotes energy transfer to PbS, and type II promotes carrier separation across the interface.…”
mentioning
confidence: 99%
“…Some other promising chalcogenide QDs and emerging 2D QDs are also introduced. 79 with permission from the American Chemical Society.…”
Section: Advantages Of Heterogeneous Hybridizationmentioning
confidence: 99%
“…4e. 79 PbS acted as effective seeding sites to promote the growth of perovskite crystals, delivering substantial morphological improvements in terms of grain size, surface coverage, and uniformity. Through analyses of time-resolved crystal formation kinetics obtained from synchrotron X-rays with a fast subsecond probing time resolution, an important "catalytic" role of the seed-like PbS NCs is clearly elucidated.…”
Section: Pbsmentioning
confidence: 99%